2010
DOI: 10.1158/1055-9965.disp-10-a80
|View full text |Cite
|
Sign up to set email alerts
|

Abstract A80: Physical activity reduces breast cancer risk in African American women

Abstract: Objective To examine the relationship between physical activity and breast cancer in African American women. Design A population-based case-control study was conducted with 199 women (97 cases and 102 controls) from the Washington, DC metro area. A self-report physical activity questionnaire elicited responses on walking for exercise and vigorous physical activity (e.g., running, aerobics, etc.) in the past year. Responses were used to calculate a metabolic equivalent (MET) score [MET-hours/week = hours/week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…In the Women's Contraceptive and Reproductive Experiences Study (CARE) (7), lifetime recreational physical activity was inversely associated with breast cancer incidence, with an odds ratio of 0.75 (95% CI 0.61-0.93) for ≥3 hours/week relative to inactivity based on 1,605 African American cases; the study found no differences by menopausal status. Breast cancer risk was inversely associated with lifetime physical activity in premenopausal and postmenopausal women in a case-control study in San Francisco that included 394 African American cases (9) and with recent exercise in two case-control studies that included 88 African American cases (10) and 97 African American cases (11). The only previous findings specific to African American women based on prospectively collected data come from the Southern Community Cohort follow-up study: based on a nested case-control study comprised largely of postmenopausal women that included 374 African American cases, neither recreational activity at baseline nor at ages 30-39 was significantly associated with breast cancer risk (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Women's Contraceptive and Reproductive Experiences Study (CARE) (7), lifetime recreational physical activity was inversely associated with breast cancer incidence, with an odds ratio of 0.75 (95% CI 0.61-0.93) for ≥3 hours/week relative to inactivity based on 1,605 African American cases; the study found no differences by menopausal status. Breast cancer risk was inversely associated with lifetime physical activity in premenopausal and postmenopausal women in a case-control study in San Francisco that included 394 African American cases (9) and with recent exercise in two case-control studies that included 88 African American cases (10) and 97 African American cases (11). The only previous findings specific to African American women based on prospectively collected data come from the Southern Community Cohort follow-up study: based on a nested case-control study comprised largely of postmenopausal women that included 374 African American cases, neither recreational activity at baseline nor at ages 30-39 was significantly associated with breast cancer risk (8).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the few studies of physical activity and breast cancer among African American women are inconsistent (7-11). Data on physical activity in relation to molecular subtype of breast cancer are also sparse and inconsistent (7, 12-19).…”
Section: Introductionmentioning
confidence: 99%
“…Several lifestyle factors including participation in physical activity and consuming a healthy diet have been deemed potential protective factors that may help to reduce a woman's risk for breast cancer; alternatively, obesity is considered a risk factor for developing postmenopausal breast cancer. Obesity is also associated with increased risk for breast cancer recurrence and increased cancer mortality 25 , increased risk of comorbidities 6,7 and poor quality of life and physical functioning 8,9 . Considering there have been substantial increases in the percentage of the US adult population who are overweight and obese over the years, with the greatest increases observed among African American women 10 , strategies to improve dietary habits among this minority population should be a priority.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the women who exercised applied for the early diagnosis of breast cancer more. Exercise is known to protect people against a number of diseases, including breast cancer (Sheppard et al, 2011). This is important because it indicates that women who exercise are health-conscious.…”
mentioning
confidence: 99%